2009
DOI: 10.1002/humu.20992
|View full text |Cite
|
Sign up to set email alerts
|

PORCNmutations in focal dermal hypoplasia: coping with lethality

Abstract: The X-linked dominant trait focal dermal hypoplasia (FDH, Goltz syndrome) is a developmental defect with focal distribution of affected tissues due to a block of Wnt signal transmission from cells carrying a detrimental PORCN mutation on an active X-chromosome. Molecular characterization of 24 unrelated patients from different ethnic backgrounds revealed 23 different mutations of the PORCN gene in Xp11.23. Three were microdeletions eliminating PORCN and encompassing neighboring genes such as EBP, the gene asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 28 publications
2
30
3
Order By: Relevance
“…GS was long presumed to be lethal in males 13, 14. However, later reports have shown that approximately 10% of all GS patients are males 2, 15. The majority of surviving males can be explained by mosaicism for PORCN mutations that arise postzygotically during embryogenesis 16 or Klinefelter syndrome, since these males carry an additional X chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
“…GS was long presumed to be lethal in males 13, 14. However, later reports have shown that approximately 10% of all GS patients are males 2, 15. The majority of surviving males can be explained by mosaicism for PORCN mutations that arise postzygotically during embryogenesis 16 or Klinefelter syndrome, since these males carry an additional X chromosome 5.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic PORCN variants have previously been reported that affect the same transmembrane domain, which further supports the pathogenicity of the p.(Gly157Asp) variant. 5,[19][20][21] Variants in PORCN were first reported as a cause of FDH in 2007. 19, 22 Froyen et al later identified PORCN variants and gene deletions in a cohort of patients with a clinical diagnosis of FDH.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of FDH patients are females, and all male patients carry postzygotic mutations, making them mosaic for Porcn function. The absence of zygotic mutant male patients indicates likely embryonic lethality caused by complete lack of Porcn function in humans (Bornholdt et al, 2009). We have recently identified Porcn in a screen for X-chromosomal embryonic lethal genes in the mouse (Cox et al, 2010), providing evidence that Porcn is indeed required for mammalian embryonic development.…”
Section: Introductionmentioning
confidence: 98%